Goal Orientation Differentiation in Visually Impaired Athletes, by Level of Visual Impairment. (May 2022) - Alemdağ, Ceyhun; Ofluoğlu, Gamze
Introduction: Athletes, who aim for even more perfection at every turn, have some orientations while achieving these goals. These orientations have been aimed to be explained with the goal orientation theory for many years. This study aims to examine the task orientation and ego orientation of visually impaired futsal players based on the level of their impairment.Methods: The sample of the study consisted of 54 visually impaired male athletes (64.8%-B2, 35.2%-B3) who participated in B2–B3 Futsal 2nd League matches in the 2018–2019 season. The Task and Ego Orientation in Sport Questionnaire was used as the data collection tool in the research (Toros, 2004 ). The data were analyzed using Mann–Whitney U test.Results: Within the scope of the research, it was found that the task orientation of the athletes with B2-level visual impairment was higher than that of the athletes with B3-level visual impairment. However, this difference was not statistically significant ( p > 05). In terms of ego orientation, on the other hand, it was determined that the ego orientation of the athletes with B3-level visual impairment was significantly higher than the athletes with B2-level visual impairment ( p < .05).Discussion: In this study, considering that athletes with B3-level visual impairment (whose vision is better than B2 athletes) perceive themselves as more competent, it may be better understood why their ego orientation scores were higher. Ego orientation here is associated with visual acuity and, therefore, self-efficacy.Implications for practitioners: In future studies, goal-orientation theory may be examined for visually impaired athletes in different sports branches (for visually impaired people, e.g., athletics, B1 football, B2-B3 futsal, goalball, judo, swimming, and weightlifting). Besides, the relevant theory would become stronger when different disability groups in the sports environment are brought into research.